Development and clinical implementation of a new template for MRI-based intracavitary/interstitial gynecologic brachytherapy for locally advanced cervical cancer: from CT-based MUPIT to the MRI compatible Template Benidorm. Ten years of experience - Villalba, Silvia Rodríguez; Sancho, Jose Richart; Palacín, Antonio Otal; Perez-Calatayud, Jose; Ortega, Manuel Santos (Journal of Contemporary Brachytherapy, 2016)
Purpose : To study outcome and toxicity in 59 patients with locally advanced cervix carcinoma treated with computed tomography (CT)-based Martinez universal perineal interstitial template (MUPIT) and the new magnetic resonance imaging (MRI)-compatible template Benidorm (TB). Material and methods: From December 2005 to October 2015, we retrospectively analyzed 34 patients treated with MUPIT and 25 treated with the TB. Six 4 Gy fractions were prescribed to the clinical target volume (CTV) combined with external beam radiotherapy (EBRT). The organs at risk (OARs) and the CTV were delineated by CT scan in the MUPIT implants and by MRI in the TB implants. Dosimetry was CT-based for MUPIT and exclusively MRI-based for TB. Dose values were biologically normalized to equivalent doses in 2 Gy fractions (EQD2). Results : Median CTV volumes were 163.5 cm3 for CT-based MUPIT (range 81.8-329.4 cm3) and 91.9 cm3 for MRI-based TB (range 26.2-161 cm3). Median D90 CTV (EBRT + BT) was 75.8 Gy for CT-based MUPIT (range 69-82 Gy) and 78.6 Gy for MRI-based TB (range 62.5-84.2). Median D2cm3 for the rectum was 75.3 Gy for CT-based MUPIT (range 69.8-132.1 Gy) and 69.9 Gy for MRI-based TB (range 58.3-83.7 Gy). Median D2cm3 for the bladder was 79.8 Gy for CT-based MUPIT (range 71.2-121.1 Gy) and 77.1 Gy for MRI-based TB (range 60.5-90.8 Gy). Local control (LC) was 88%. Overall survival (OS), disease free survival (DFS), and LC were not statistically significant in either group. Patients treated with CT-based MUPIT had a significantly higher percentage of rectal bleeding G3 (p = 0.040) than those treated with MRI-based TB, 13% vs. 2%. Conclusions : Template Benidorm treatment using MRI-based dosimetry provides advantages of MRI volume definition, and allows definition of smaller volumes that result in statistically significant decreased rectal toxicity compared to that seen with CT-based MUPIT treatment.